2013
DOI: 10.1089/ten.tea.2012.0047
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells or Their Conditioned Medium Prevents Bone Loss in Ovariectomized Nude Mice

Abstract: Umbilical cord blood (UCB) has recently been recognized as a new source of mesenchymal stem cells (MSCs) for use in stem cell therapy. We studied the effects of systemic injection of human UCB-MSCs and their conditioned medium (CM) on ovariectomy (OVX)-induced bone loss in nude mice. Ten-week-old female nude mice were divided into six groups: Sham-operated mice treated with vehicle (Sham-Vehicle), OVX mice subjected to UCBMSCs (OVX-MSC), or human dermal fibroblast (OVX-DFB) transplantation, OVX mice treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 47 publications
0
47
0
1
Order By: Relevance
“…An et al, demonstrated a 30% increase in bone mineral density (BMD) when human UBC-MSCs were injected in OVX mice after 4 and 8 weeks. They also observed increases in trabecular volume, number and thickness in OVX mice treated with hUB-MSCs [101].…”
Section: Stem Cell Therapy For Treating Osteoporosismentioning
confidence: 85%
“…An et al, demonstrated a 30% increase in bone mineral density (BMD) when human UBC-MSCs were injected in OVX mice after 4 and 8 weeks. They also observed increases in trabecular volume, number and thickness in OVX mice treated with hUB-MSCs [101].…”
Section: Stem Cell Therapy For Treating Osteoporosismentioning
confidence: 85%
“…Bone formation by umbilical cord-derived MSCs (UC-MSCs) was demonstrated in vivo by Diao and collaborators who loaded human UC-MSCs into scaffolds that were transplanted subcutaneously into BALB/c nude mice, observing efficiently bone formation by UC-MSCs [159]. [160] used OVX nude mice as a model to study the influence of systemic injection of human umbilical cord blood hUCB-MSCs. After the infusion, the BMD levels enhanced considerably and the micro-CT analysis of the mice tibiae exhibited considerably greater values of trabecular number and thickness, as well as bone volume.…”
Section: Umbilical Cord Derived Mscs (Uc-mscs)mentioning
confidence: 99%
“…In this study, human UC‐MSCs can proficiently form bone after transplantation in 12 weeks. An et al () studied the influence of systemic injection of umbilical cord blood (UCB)‐MSCs to OVX mice. Four and 8 weeks after the infusion, the BMD levels enhanced considerably.…”
Section: Stem Cell‐based Therapy For Osteoporosismentioning
confidence: 99%